PENGARUH PENYAJIAN LAPORAN KEUANGAN DAERAH DAN AKSESIBILITAS LAPORAN KEUANGAN DAERAH TERHADAP TRANSPARANSI DAN AKUNTABILITAS PENGELOLAAN KEUANGAN DAERAH KABUPATEN SIMALUNGUN - Saragih, Charli Andreas; Ratnawati, Vince; Hanif, Rheny Afriana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to test the effect of regional financial statement presentation and accessibility of financial statement for transparency and accountability in financial management. The study was conducted in Simalungun district. Sample in this research are employee of SKPD in Government of Simalungun. The sampling technique using purposive sampling method and there are 62 respondents. The data of this research using primary data directly through a questionnaire and analyzed using SPSS 17. The data were analyzed to test the hypothesis using multiple linear regression analysis approach with tools statistical program, after test the classical assumption are met. The results of this study show that the presentation of the financial report and accessibility of financial report influences on transparency and accountability of financial management of the district.Keywords: financial, accessibility, transparency, and accountability